Reading between life and work: reflections on 'J.M. Coetzee'. Issue 3 (15th April 2016) - Boehmer, Elleke
Abstract : JM Coetzee has remarked that all autobiography is story-telling and also that all writing is a kind of autobiography. Exploring this link between (auto)biography, and fiction as 'writing', this essay will offer critical reflections on J.M. Coetzee's longstanding life-writing or 'autre-fictional' project as it intersects with two recent biographical studies, John Kannemeyer's J.M. Coetzee: A Life in Writing (2012), and David Attwell's J.M. Coetzee and the Life of Writing: Face to Face with Time (2015). I will consider the links that are drawn between the author's life and his writing in the Kannemeyer biography and in Attwell's book historical study, and will set these against the interplay between self-masking and self-retrospection that marks Coetzee's oeuvre, not least the Scenes from Provincial Life trilogy. This reading will shed light on the tireless oscillation in Coetzee's work between the 'expressive function' of language on the one hand, and the concealment that metaphor and symbolization allow on the other .